2023
DOI: 10.3390/ijms24032416
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Visual Prognosis of Patients Following Lens-Sparing Vitrectomy for Stage 4A Retinopathy of Prematurity

Abstract: This study evaluated the long-term visual outcomes of patients in whom at least one eye underwent successful lens-sparing vitrectomy (LSV) for stage 4A retinopathy of prematurity (ROP). A retrospective chart review was conducted using the data of 61 eyes of 42 patients with a minimum 4-year follow-up after successful LSV, with or without anti-vascular endothelial growth factor (VEGF) therapy, and whose best-corrected visual acuity (BCVA) was measurable using Landolt rings at the final visit. The mean age at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…aforementioned studies. It can be seen that the BW was close to the results of Chandra et al, 9 while it was more than that reported by Iwahashi et al, 10 this point was mentioned before by Vinekar et al, in India back in 2007, where they stated that the BW of children with ROP may be higher in developing countries. 11 In addition, a recent study (2022) in Egypt, a developing Arab country, by Noor et al, reported that the mean BW of ROP infants was 1,900±562.2 g, 12 and this could be attributed to the differences that cause an unstable clinical course in infants-of-developing countries, regardless having GA of more than 30 weeks or BW of more than 1,500 grams.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…aforementioned studies. It can be seen that the BW was close to the results of Chandra et al, 9 while it was more than that reported by Iwahashi et al, 10 this point was mentioned before by Vinekar et al, in India back in 2007, where they stated that the BW of children with ROP may be higher in developing countries. 11 In addition, a recent study (2022) in Egypt, a developing Arab country, by Noor et al, reported that the mean BW of ROP infants was 1,900±562.2 g, 12 and this could be attributed to the differences that cause an unstable clinical course in infants-of-developing countries, regardless having GA of more than 30 weeks or BW of more than 1,500 grams.…”
supporting
confidence: 82%
“…The mean GA at time of surgery was 39.6±2.3 weeks (duration from birth until surgery was 10.2±2.0 weeks), and their mean BW was 1046.9±216.6 g. These results were comparable to results of Chandra et al in India, who studied 60 eyes of 30 babies who had stage 4 ROP, and reported that the mean GA at time of surgery was 40.8±2.2 weeks, and their birth weight was 1,214.5±329.7 g. 9 In another study done by Iwahashi et al in Japan, LS-vitrectomy outcomes were studied in 61 eyes of 42 infants that had stage 4a ROP, and the reported GA at surgery was 41.4±5.9 years and their BW was 681.9±234.7 g. 10 It is important to study the GA at surgery in order to know where we stand comparing to works done in other developing and developed countries, although the indications are almost the same in patients with stages 4 and 5, the rapid action and the decision to operate may differ, however, the GA at surgery was very close between our study and the aforementioned studies. It can be seen that the BW was close to the results of Chandra et al, 9 while it was more than that reported by Iwahashi et al, 10 this point was mentioned before by Vinekar et al, in India back in 2007, where they stated that the BW of children with ROP may be higher in developing countries. 11 In addition, a recent study (2022) in Egypt, a developing Arab country, by Noor et al, reported that the mean BW of ROP infants was 1,900±562.2 g, 12 and this could be attributed to the differences that cause an unstable clinical course in infants-of-developing countries, regardless having GA of more than 30 weeks or BW of more than 1,500 grams.…”
Section: Discussionmentioning
confidence: 99%